Strategi Kepala Kementrian Agama Kabupaten Pangandaran Dalam Mengembangkan Kurikulum Darurat Diniyah Takmiliyah Di Pangandaran Pada Masa Pandemi Covid-19 - Dasep S. Ubaidillah; Irpan Ilmi (Proceedings of Annual Conference on Islamic Educational Management, 2021)
The world order has changed due to the COVID-19 pandemic. The economic, cultural, political, social and education sectors have been affected by the COVID-19 impact. Education is the main mouthpiece in improving human resources. Superior resources will give birth to superior products. Thus, the COVID-19 pandemic requires the government, especially the Ministry of Education, Culture, Research and Technology and the Ministry of Religion to conduct studies related to education policies during the Covid-19 pandemic. This study used qualitative research methods. Qualitative methods emphasize the observation of events and enter into the substance of the meaning of each event. Qualitative research is focused on human elements, objects, and institutions, as well as relationships or interactions between elements in an effort to understand an event, behavior, and event or activity. The strategy of the Pangandaran Regency Ministry of Religion in developing the diniyah takmiliyah curriculum is to coordinate with supervisors, madrasa heads in Pangandaran Regency. The implementation of the diniyah curriculum development during the COVID-19 period was based on the decision of the directorate of Islamic education number 2791 of 2020 instructing to develop curriculum in madrasas. The development of the diniyah takmiliyah curriculum in the Pangandaran district is based on the Minimum Competency Assessment (AKM), Character Survey and Learning Environment Survey which is charged to supervisors and madrasa heads.